Some Generalizations of Jungck's Fixed Point Theorem - J. R. Morales; E. M. Rojas (International Journal of Mathematics and Mathematical Sciences)
We are going to generalize the Jungck's fixed point theorem for commuting mappings by mean of the concepts of altering distance functions and compatible pair of mappings, as well as, by using contractive inequalities of integral type and contractive inequalities depending on another function.